2021
DOI: 10.1155/2021/6717582
|View full text |Cite|
|
Sign up to set email alerts
|

Human Glioma Cells Therapy Using ATRA-Induced Differentiation Method to Promote the Inhibitive Effect of TMZ and CCDP

Abstract: The glioma stem cells (GSCs) performed the self-renewal, proliferation, and differentiation characteristics; their drug resistance has become the main reason for glioma clinical treatment failure. All-trans retinoic acid (ATRA) is an important inducer of cell differentiation, applied in the treatment of hematologic diseases and other solid tumors. ATRA is a fat-soluble compound, which can easily go through the blood-brain barrier. Therefore, in this study, ATRA was used to induce the differentiation of glioma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Notably, several studies have demonstrated the close relationship between the extracellular matrix (ECM) and drug resistance in various cancers. Changes in the ECM structure in glioblastoma (GBM) have been shown to increase resistance to temozolomide (TMZ) treatment [29][30][31]. GBM cells can also modify the ECM by secreting hyaluronic acid, which enhances resistance to lysovirus treatment [31].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several studies have demonstrated the close relationship between the extracellular matrix (ECM) and drug resistance in various cancers. Changes in the ECM structure in glioblastoma (GBM) have been shown to increase resistance to temozolomide (TMZ) treatment [29][30][31]. GBM cells can also modify the ECM by secreting hyaluronic acid, which enhances resistance to lysovirus treatment [31].…”
Section: Discussionmentioning
confidence: 99%
“…19 Strong antineoplastic and cyto-differentiating activities for ATRA have been demonstrated in myelodysplastic diseases and solid cancers such as lung, breast and prostate carcinomas as well as brain tumours. 20,21 ATRA can suppress the proliferation of primary/metastatic cells in skin neoplasms such as melanoma and inhibit tumour growth in melanoma patients, as documented in clinical trials. 22 We aimed to evaluate the impact of ATRA treatment on MCC cells.…”
mentioning
confidence: 91%
“…ATRA drives tumour cell differentiation by modulating the retinoid signalling, leading to anti‐proliferative/pro‐apoptotic effects 19 . Strong antineoplastic and cyto‐differentiating activities for ATRA have been demonstrated in myelodysplastic diseases and solid cancers such as lung, breast and prostate carcinomas as well as brain tumours 20,21 . ATRA can suppress the proliferation of primary/metastatic cells in skin neoplasms such as melanoma and inhibit tumour growth in melanoma patients, as documented in clinical trials 22 …”
Section: Introductionmentioning
confidence: 97%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%